1999
DOI: 10.1016/s1090-5138(99)00015-x
|View full text |Cite
|
Sign up to set email alerts
|

Population Migration and the Variation of Dopamine D4 Receptor (DRD4) Allele Frequencies Around the Globe

Abstract: This article reports an association between the variation of dopamine D4 receptor (DRD4) allele frequencies around the globe and population migration patterns in prehistoric times. After compiling existing data on DRD4 allele frequencies of 2,320 individuals from 39 populations and on the migration pattern of these groups, we found that, compared to sedentary populations, migratory populations showed a higher proportion of long alleles for DRD4. The correlation between macro-migration (long-distance group migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
182
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 257 publications
(195 citation statements)
references
References 39 publications
10
182
1
2
Order By: Relevance
“…Bottlenecks certainly have occurred during human migration and evolution (33)(34)(35) and undoubtedly have influenced the current worldwide DRD4 allele frequency. Numerous population studies on other genes (24,33,35) have shown that an ''out-ofAfrica'' constriction of allele diversity (and an increase in LD) likely occurred.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bottlenecks certainly have occurred during human migration and evolution (33)(34)(35) and undoubtedly have influenced the current worldwide DRD4 allele frequency. Numerous population studies on other genes (24,33,35) have shown that an ''out-ofAfrica'' constriction of allele diversity (and an increase in LD) likely occurred.…”
Section: Resultsmentioning
confidence: 99%
“…drove the expansion (and partial replacement). The speculation that migration could account for the current 7R allele distribution has been proposed (34). In addition to such phenotypic selection, sexual selection could be operating as well.…”
Section: Resultsmentioning
confidence: 99%
“…It is even more difficult to imagine that in all three archipelagos, all founding populations exhibited coincidentally similar patterns of extraversion and openness. Chen, Burton, Greenberger, and Dmitrieva (1999) have advocated selective mortality to explain personality evolution. These authors examined large samples of populations worldwide, who had emigrated several thousand miles during human history (hundreds of generations).…”
Section: Third Theoretical Issue: Which Is the Biological Force By Mementioning
confidence: 99%
“…It has been the subject of intense interest in psychiatry, because bearers of one variant are at increased risk for attention deficit hyperactivity disorder (ADHD) (1). A survey of world frequencies of DRD4 alleles has shown striking differences among populations (2), with population differences greater than those of most neutral markers. In this issue of PNAS Ding et al (3) provide a detailed molecular portrait of world diversity at the DRD4 locus.…”
mentioning
confidence: 99%
“…What we see today looks much more likely to be the consequence of some kind of frequency-dependent selection, in which the frequency of the new allele increases up to a certain point and then stabilizes. These selective forces must not be the same in all populations, because the 7R allele is quite common in some populations (South American Indians), exists at intermediate frequencies in others (Europeans and Africans), and is rare to nonexistent in yet others (East Asia, !Kung Bushmen) (2).…”
mentioning
confidence: 99%